A randomized, placebo-controlled, double-blind study on the effects of (−)-epicatechin on the triglyceride/HDLc ratio and cardiometabolic profile of subjects with hypertriglyceridemia: Unique in vitro effects. (15th November 2016) - Gutiérrez-Salmeán, Gabriela; Meaney, Eduardo; Lanaspa, Miguel A.; Cicerchi, Christina; Johnson, Richard J.; Dugar, Sundeep; Taub, Pam; Ramírez-Sánchez, Israel; Villarreal, Francisco; Schreiner, George; Ceballos, Guillermo
Abstract: Background: Cardiometabolic disruptions such as insulin resistance, obesity, high blood pressure, hyperglycemia, and dyslipidemias, are known to increase the risk for cardiovascular and metabolic diseases such as type 2 diabetes mellitus and atherosclerosis. Several screening tools for assessing cardiometabolic risk have been developed including the TG/HDLc ratio, which has been, demonstrated to possess a strong association with insulin resistance and coronary disease. Dietary modifications, together with regular moderate exercise have proven to be effective in attenuating cardiometabolic disruptions. However, they often exhibit poor long-term patient compliance. Nutraceutics, including (−)-epicatechin (EPI), have gained increasing interest as coadjuvant effective and safe therapies that are able to attenuate hypertension, hyperglycemia, hyperinsulinemia, hypertriglyceridemia and hypoalphalipoproteinemia. Methods: The aims of this study were: 1) to compare the in vitro effect of EPI vs. (+)-catechin on fructose induced triglyceride accumulation and mitochondrial function in Hep2 cells in culture, 2) to evaluate the efficacy of EPI treatment in reducing fasting blood triglycerides and improving the TG/HDLc ratio in hypertriglyceridemic patients with a total daily dose of 100 mg of EPI. Secondary clinical variables included total cholesterol, LDLc, fructosamine, glucose, insulin, and high sensitivity C-reactive protein blood levels. Results and conclusion: Our results provide preliminary evidence as to favorable effects of EPI on glycemia homeostasis, lipid profile and systemic inflammation such bioactive actions are not class-effects (i.e. limited to their antioxidant potential) but instead, may result from the specific activation of associated downstream signaling pathways since catechin has no effects.